2012
DOI: 10.2174/157341112798472224
|View full text |Cite
|
Sign up to set email alerts
|

Isolation and Identification of an Angiotensin-I Converting Enzyme Inhibitory Peptide from Yeast (Saccharomyces cerevisiae)

Abstract: Angiotensin-I converting enzyme (ACE) has an important function in blood pressure regulation. ACEinhibitory peptides can lower blood pressure by inhibiting ACE activity. In this investigation, water-soluble proteins were extracted from yeast (Saccharomyces cerevisiae) and hydrolyzed by yeast protein extraction enzyme to isolate ACEinhibitory peptides. Peptides with ACE-inhibitory activity were further separated and purified by ultrafiltration and fast protein liquid chromatography (FPLC). A hexapeptide, Thr-Pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 11 publications
0
15
0
Order By: Relevance
“…TPTQQS has been shown to be an effective ACE-inhibitory peptide that was isolated from hydrolyzed yeast protein in our previous study [16] . However, the amino acid sequence of this peptide is not in accordance with the results of structure-activity correlation studies on ACE-inhibitory peptides [11] .…”
Section: Discussionmentioning
confidence: 95%
See 2 more Smart Citations
“…TPTQQS has been shown to be an effective ACE-inhibitory peptide that was isolated from hydrolyzed yeast protein in our previous study [16] . However, the amino acid sequence of this peptide is not in accordance with the results of structure-activity correlation studies on ACE-inhibitory peptides [11] .…”
Section: Discussionmentioning
confidence: 95%
“…The active cleft divides tACE into two structural subdomains: subdomain I and subdomain II. The peptide was adjacent to subdomain I, far from the active site, which includes the important positions S1′ and S2′, especially [16] .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The method was referred to Ni(2012) with some modifications, the method was conducted as follows: yeast powder (1:15 w/V) was added to distilled water, then adjusted to pH 7.7, incubated at 60°C for 30 minutes after that. In the next step, the solutions were treated with yeast protein extraction enzyme (3.5% w/w), and the protein was extracted with shaking for 6 hours.…”
Section: Preparation Of Hydrolysates From Yeast Protein By Enzymatic mentioning
confidence: 99%
“…Because of their confirmed or suspected association with side effects such as taste disturbances, cough and skin rashes, the tendency for aCE inhibitorrelated research is going progressively toward the development of non-toxic and natural substitutions. During the last decade, studies have focused on the production and isolation of peptides with potent aCE inhibitory activity from various sources, including lysozyme [7], casein [8], soya milk [9], collagen and gelatin [10], bovine brisket [11], fish [12,13] and production by fermentation [14,15]. Studies suggested that natural peptides consisting of two or three amino acids have higher affinities with tissues, becoming absorbed and assimilated more easily, than the recognized inhibitor such as captopril [16,17].…”
Section: Introductionmentioning
confidence: 99%